State of the art: strategies for extracorporeal membrane oxygenation in respiratory failure. (October 2012) - Rehder, Kyle J; Turner, David A; Bonadonna, Desiree; Walczak Jr, Richard J; Cheifetz, Ira M
Extracorporeal membrane oxygenation (ECMO) is an important rescue therapy for patients with cardiac and/or respiratory failure, with a growing body of literature supporting its use. Despite widespread use of ECMO, there remains a paucity of data on optimal management strategies for ECMO patients. Management of ECMO patients involves an understanding of the complex interaction between this technology and the critically ill patients being supported. ECMO providers typically rely on a combination of consensus guidelines and institutional experience to make management decisions. Substantial controversy continues to exist regarding many elements of ECMO management, including seemingly straightforward decisions such as the initial implementation of this technology. In addition, there are multiple providers involved in the management of ECMO patients who must be co-ordinated for this supportive therapy to be most effective. This manuscript provides an overview of current techniques for treating respiratory ECMO patients.